La crisis del modelo de Estado en España y la reforma federal - Jorge Cagiao y Conde (Cahiers de Civilisation Espagnole Contemporaine)
The Spanish State of Autonomies has been suffering from a deep crisis for several years. If the reasons for the crisis may be found in the Constitution of 1978, its aggravation depends foremost of the maladjustment of the Spanish system to its very complex political context. In this paper, the author explains the causes of the crisis of the Spanish form of State. First, he deals with some of the juridical vices of its decentralized system. Secondly, he comments on the problems generated by the passive attitude of Spanish governments to adapt the constitutional system to its conflictual context (multinational in public law and multi-level into the UE system), and he also explains why the federal logic is probably the answer to the internal and external factors of State crisis. In the author’s opinion, the federal principle should lead the constitutional reform of the State, as he notes in the last section of this paper